Mathematical Performance of American Youth: Diminished Returns of Educational Attainment of Asian-American Parents - Assari, Shervin (Educ Sci (Basel), 2020)
The Marginalization-related Diminished Returns (MDR) phenomenon refers to the weaker effects of parental educational attainment for marginalized groups, particularly ethnic minorities. This literature, however, is limited to Blacks and Hispanics; thus, it is not clear if the MDR phenomenon also applies to the educational performance of Asian Americans or not. To explore ethnic differences in the association between parental educational attainment and youth mathematical performance among 10th-grade American high schoolers, this cross-sectional study used baseline data from the Education Longitudinal Study, a national survey of 10th-grade American youth. The analytical sample included a total number of 10,142 youth composed of 1460 (14.4%) Asian-American and 8682 (85.6%) non-Hispanic youth. The dependent variable was youth math performance (standard test score). The independent variable was parental education. Gender, both parents living in the same household, and school characteristics (% students receiving free lunch, urban school, and public school) were the covariates. Ethnicity was the moderating variable. Linear regression was used for data analysis. Overall, parental educational attainment was positively associated with math ability (test score). We observed a statistically significant interaction between ethnicity (Asian American) and parental education attainment on the results of math test scores, indicating that the boosting effect of high parental educational attainment on youth math function is smaller for Asian-American youth than for Non-Hispanic White youth. While high parental educational attainment contributes to youth educational outcomes, this association is weaker for Asian-American youth than non-Hispanic White youth. Diminished returns (weaker effects of parental education in generating outcomes for ethnic minorities) that are previously shown for Hispanics and Blacks also apply to Asian Americans.